Pengaruh Supply Chain Management Terhadap Kinerja Oprasional - Renhart Purba; Anis Rachma Utary; Doddy Adhimursandi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study was to determine the influence of process information, transaction costs, inventory integrity and sharing information on the operational performance of the company. This research was conducted at HPI furniture that was in the county darts. The sampling method by using purposive sampling, with a population that used as many as 152 SMEs and samples collected as many as 50 as the owner of the SME furniture. The data in this study using primary data, interviews and questionnaires. Hypothesis test used in this study is Multiple Linear Regression using SPSS version 20. The results of this study show that: 1) The process of information positive and significant effect on the company's operational performance IKM furniture in county darts, 2) Transaction costs a significant negative effect on the company's operational performance IKM furniture in county darts, 3) Integration supplies positive and significant effect the company's operational performance in county darts furniture IKM, 4) information sharing and significant positive effect on the operating performance of SMEs in the furniture district darts.